a)
[tex]x + ( - 6x + 4) = - 5x + 4 \\ x - ( - 6x + 4) = 7x - 4[/tex]
b)
[tex]8 + ( - (4y + 5)) = 8 - 4y - 5 = \\ = - 4y + 3 \\ 8 - ( - (4y + 5) = 8 + 4y + 5 = \\ = 4y + 13[/tex]
c)
[tex] {a}^{2} - 4 + 8 - {a}^{2} = 4 \\ {a}^{2} - 4 - (8 - {a}^{2} )2 {a}^{2} - 12[/tex]
d)
[tex]2x - y + ( - (x - 2y)) = \\ = 2x - y - x + 2y = x + y \\ 2x - y - ( - x + 2y) = \\ = 2x - y + x - 2y = 3x - 3y[/tex]
e)
[tex] - 2a + b + 2a + b = 2b \\ - 2a + b - (2a + b) = - 4a[/tex]
f)
[tex] - a + b + ( - a - b) = - 2a \\ - a + b - ( - a - b) = 2b[/tex]